2012
DOI: 10.1002/nau.22295
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of lower urinary tract symptoms (LUTS) and overactive bladder (OAB) by racial/ethnic group and age: Results from OAB‐POLL

Abstract: Aims To estimate the prevalence of LUTS and OAB in a large, ethnically diverse US study. Methods This cross‐sectional, population‐representative survey was conducted via the Internet in the US among 10,000 men and women aged 18–70 (2,000 African‐Americans [AA], 2,000 Hispanics, 6,000 whites). The LUTS tool assessed how often participants experienced LUTS during the past 4 weeks on a five‐point Likert scale. OAB was defined by the presence of urinary urgency ≥ “sometimes” or ≥ “often,” and/or the presence of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
4
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(209 citation statements)
references
References 29 publications
7
190
4
8
Order By: Relevance
“…3,4 Prevalence and severity of OAB are known to increase with age from 14.9% in the 18-to 29-year group, to 21.3% in the 30-to 39-year group, 32.9% in the 40-to 49-year group, 35.8% in the 50-to 59-year group and up to 39.8% in the 60-to 69-year group. 5 With the increase in longevity owing to advances in health care and the population growth, the burden of OAB is going to increase in the next few decades, with a 9% increase anticipated from 500 million globally in 2013 to 546 million by 2018. 6 Two-thirds of a predominantly female sample of people with OAB had sought treatment in the 6 months prior to a multinational survey.…”
Section: Definition and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Prevalence and severity of OAB are known to increase with age from 14.9% in the 18-to 29-year group, to 21.3% in the 30-to 39-year group, 32.9% in the 40-to 49-year group, 35.8% in the 50-to 59-year group and up to 39.8% in the 60-to 69-year group. 5 With the increase in longevity owing to advances in health care and the population growth, the burden of OAB is going to increase in the next few decades, with a 9% increase anticipated from 500 million globally in 2013 to 546 million by 2018. 6 Two-thirds of a predominantly female sample of people with OAB had sought treatment in the 6 months prior to a multinational survey.…”
Section: Definition and Prevalencementioning
confidence: 99%
“…One of the difficulties often encountered during UDS is the ability to identify artefacts and interpret the results. 5 One of the key aspects of maintaining the accuracy of UDS is to ensure that the initial resting pressures are correct and recognised. 8 Previous studies showed that even under ideal test-retest conditions, reliability can be poor for many urodynamic parameters.…”
Section: Standardisation Of the Urodynamic Assessmentmentioning
confidence: 99%
“…1,2 Bladder symptoms, such as incontinence, urgency, or frequency, are commonly associated with a lower quality of life and increased use of healthcare resources. [3][4][5][6][7] Bladder symptoms may be due to age-related autonomic denervation, decreased bladder muscle tone, or increased bladder muscle fatigue. 8 Parity and medical conditions, such as diabetes, obesity, and depression, are associated with prevalence and incidence of bladder symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have shown that vitamin D elicits a robust anti-inflammatory response in human myometrial cells [99]. Coyne et al has demonstrated the prevalence of OBS in the total United States population and found that black women had a higher prevalence (32.6%), compared to Hispanic (29%) and white women (29.4%) [100].…”
Section: Vitamin D and Overactive Bladdermentioning
confidence: 75%